Efeito do resveratrol nas alterações comportamentais induzidas por flufenazina em ratos e sua interação com a enzima monoaminoxidase in silico e in vitro - Busanello, Alcindo (2016)
Typical antipsychotics, commonly used to schizophrenia treatment, cause tardive dyskinesia in humans and orofacial dyskinesia (OD) in rodents. In the present work, we investigated the effects of resveratrol, a polyphenol with neuroprotective properties mainly found in red fruits and wine, on the behavioral alterations induced by acute and chronic treatment with fluphenazine in rats. Furthermore, we evaluated the effects of resveratrol on the enzyme monoaminoxidade (MAO) in vitro, in silico and the participation of MAO in OD. Thus, the first aim of the present study was to investigate the action of resveratrol (using a low dose), in an acute model of vacuous chewing movements (VCMs) induced by the administration of fluphenazine in rats. In this study, we observed that resveratrol, at a dose of 1 mg/kg administered 3 times a week during 21 days, reduced the prevalence of VCMs, but not the intensity of OD, represented by number of VCMs. The treatment with fluphenazine reduced the locomotor and exploratory activity in open field and the co-treatment with resveratrol protected partially. As some studies suggest that MAO enzyme is a possible target of resveratrol, the second aim was to evaluate the effects of resveratrol on MAO activity in vitro and in silico. Resveratrol inhibits both isoforms of MAO, however with a potency approximately of 28 times higher to MAO-A than MAO-B. The data from analyse of kinetic of inhibition of MAO in the presence of resveratrol showed an alteration in Vmax without alter the Km, indicating a non competitive profile of inhibition to MAO-A as well as MAO-B. Furthermore, a profile partially reversible to MAOA and completely reversible to MAO-B was obtained. In in silico study using the human enzyme, both isoforms of resveratrol interacted with the active site of enzyme avoiding the entry of substrate, the cis-resveratrol to MAOA, and the trans-resveratrol to MAO-B. Hydroxyl groups from resveratrol in the H-bonds of the enzymes can be responsible for the affinity with them. The third aim of this work was to investigate the effects of resveratrol, administered in drinking water at a dose of 20 mg/kg, in a chronic model of OD (126 days) induced by fluphenazine in rats, as well as evaluate if alterations on MAO activity could be involved in the possible protective effect of resveratrol. Fluphenazine reduced the body weight gain and the locomotor and exploratory activity of the animals and the co-treatment with resveratrol did not alter these parameters. The chronic treatment with fluphenazine increased the number of VCMs and the co-treatment with resveratrol reduced the intensity of VCMs. With regard to MAO, only the striatal activity of MAO-B in the group treated with fluphenazine decreased in relation to resveratrol group. In general, the results suggest that the tested doses of resveratrol were efficacious in reduce OD in rats. Besides resveratrol had inhibited the activity os MAO in vitro, it is probable that its effects were not dependents of a direct action of resveratrol on the activity of this enzyme.